Environmental Conservation in Quraish Shihab and Hamka’s Perspective - Syarifah, Umaiyatus; Azizy, Jauhar; Sihabussalam, Sihabussalam (Islamadina : Jurnal Pemikiran Islam, 2024)
The environmental crisis has become a global issue and a common concern of this century. The anthropocentric paradigm is also one of the causes of environmental damage. This paradigm assumes that the center of the universe is human beings, so they are free to exploit natural resources for their interests. This paper will reveal Qur’an-based environmental conservation. The author more specifically reveals the views of the mufasir of Indonesia, M. Quraish Shihab and Buya Hamka, on the issue of environmental conservation. This paper aims to find the concept of environmental conservation based on the Qur’an by two Indonesian muftis. The research method used in this article is qualitative and is library research. The main data used in this article include Tafsir Al-Misbah by M. Quraish Shihab and Tafsir Al-Azhar by Hamka. The data were analyzed with a content analysis approach. The conclusion of this article shows that Indonesia’s mufasir is concerned about environmental conservation based on the Qur’an. M. Quraish Shihab and Buya Hamka have a common interpretation that the universe was created by Allah for humans and used to meet their needs proportionally. The concept of the caliph and its implementation (utilizing, maintaining, preserving, and regenerating nature for the next life) is urgently needed to protect the earth and its environment. Environmental preservation is contained in the concept of iá¸¥sÄn with the peak of good behavior towards nature. The concept of justice by acting in balance is a responsibility to the environment. The concept of proportionality (not excessive) in the use of the environment.